2005
DOI: 10.1038/sj.onc.1208648
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the phosphorylation and integrity of protein synthesis initiation factor eIF4GI and the translational repressor 4E-BP1 by p53

Abstract: Activation of a temperature-sensitive form of mouse p53 in murine erythroleukaemia cells rapidly inhibits protein synthesis and causes early dephosphorylation and cleavage of protein synthesis initiation factor eIF4GI and the eIF4E-binding protein 4E-BP1. Dephosphorylated 4E-BP1 and the cleaved products of 4E-BP1 and eIF4GI associate with eIF4E under these conditions, concomitant with decreased interaction of full-length eIF4GI with eIF4E. These changes may play an important role in preventing formation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 54 publications
6
58
0
1
Order By: Relevance
“…Intriguingly, cytoplasmic p53 has been found to be covalently linked to 5.8S rRNA and associated with ribosomes (Fontoura et al, 1992(Fontoura et al, , 1997. p53 induction decreases protein synthesis and S6K activity (Horton et al, 2002), but translational inhibition by p53 may occur also independently of mTOR (Constantinou and Clemens, 2005). In accordance with the former finding, Feng et al (2005) found that etoposide addition to cells resulted in downregulation of S6K activity mediated by AMPK and TSC.…”
Section: Osmotic Stresssupporting
confidence: 52%
“…Intriguingly, cytoplasmic p53 has been found to be covalently linked to 5.8S rRNA and associated with ribosomes (Fontoura et al, 1992(Fontoura et al, , 1997. p53 induction decreases protein synthesis and S6K activity (Horton et al, 2002), but translational inhibition by p53 may occur also independently of mTOR (Constantinou and Clemens, 2005). In accordance with the former finding, Feng et al (2005) found that etoposide addition to cells resulted in downregulation of S6K activity mediated by AMPK and TSC.…”
Section: Osmotic Stresssupporting
confidence: 52%
“…Electrophoresis of 4E-BP1 polyacrylamide gel separates three different isoforms: α, β and γ. The γ band represents the most highly phosphorylated band (Ser 65, Thr 70 and Thr 37/46), the β band represents phosphorylations at Thr 70 and Thr 37/46, and the α band corresponds to the least phosphorylated form, Thr 37/46 (9,21,22). To assess whether 4E-BP1, eIF4E and eIF4G might be involved in eIF4F complex formation and how their phosphorylation status could affect cell proliferation, we studied two breast carcinoma cell lines (MDA-MB 231 and MDA-MB 468) and human primary fibroblasts (IMR90).…”
Section: Resultsmentioning
confidence: 99%
“…Cell culture and treatments Murine embryonic fibroblasts, MEL cells expressing a temperature-sensitive form of p53 (Johnson et al, 1993) and Jurkat human T lymphoma cells were grown as described (Juo et al, 1998;Jeffrey et al, 2002;Constantinou and Clemens, 2005 Preparation of cell extracts Cytoplasmic extracts were prepared by washing cells in phosphate-buffered saline and re-suspending the pellets in cell lysis buffer (50 mM 4-morpholinepropanesulphonic acid (MOPS), 50 mM NaCl, 1 mM ethylenediaminetetraacetic acid (EDTA), 2.5 mM ethylene glycol bis(b-aminoethylether)-N,N,N 0 ,N 0 ,-tetraacetic acid (EGTA), 7 mM 2-mercaptoethanol, 40 mM b-glycerophosphate, 0.5% NP-40) containing the following phosphatase and proteinase inhibitors: Complete Mini, EDTAfree protease inhibitor cocktail (Roche, Lewes, Sussex, UK), 2 mM sodium vanadate, 1 mM microcystin, 1 mM phenylmethylsulphonylfluoride and 2 mM benzamidine. After 10 min at 41C the cell lysates were centrifuged for 15 min at 12 000 g to pellet the nuclei.…”
Section: Methodsmentioning
confidence: 99%